The Image of Germany on the Pages of the Newspaper “Russian Invalid” in the First Years of the World War I (1914-1915) - Vasiliy V. Frolov (Журнал Фронтирных Исследований)
The article analyzes the image of Germany, which was formed by the journalists of the domestic daily newspaper “Russian invalid” in 1914–1915, when the Russian Empire was in active military confrontation with the states of the Triple (later Quadruple) Alliance in the European Theater of Operations, and Germany was its main and most dangerous enemy on the Eastern Front. Correspondents of the “Russian Invalid”, the official printed organ of the Russian Military Ministry, in the first years of the First World War (1914–1915) on the pages of their newspaper paid special attention to the Hohenzollern Empire, its army, socio-economic and political development, direct participation German armed forces in the fighting of the Great War. The main part of the information about Germany by the authors of the publication we studied was placed in the headings “From Foreign Life”, “Public Life”, “Naval Department”, “Military Chronicle”, “Telegram” and “Articles”. At the end of the study, it was concluded that the German Empire on the pages of “Russian Invalid” appeared as the economic and military-political locomotive of the Triple (later Quadruple) Alliance, which made enormous efforts to implement the redistribution of spheres of influence in the then world and potential redistribution in its own benefit of colonial possessions.